Trends in dietary patterns of Latin American populations - Odilia I. Bermudez; Katherine L. Tucker
It is important to characterize the level and magnitude of changes in food consumption patterns in Latin American populations as they undergo demographic and developmental transitions because of the effects of such changes on the development and progression of chronic diseases. This paper examines trends in food intake across regions in Latin America. Although trends in apparent food consumption differ in magnitude and timing, the overall patterns of change are remarkably consistent. Intakes of total fat, animal products, and sugar are increasing, even while there have been rapid declines in the intake of cereals, fruit, and some vegetables. The costs of the increased prevalence of chronic disease associated with these dietary changes are already affecting health systems still coping with malnutrition and infectious disease. Because this pattern of change is predictable, it is important to learn from the experiences gained in countries that are more advanced in the transition. Efforts to educate the population on the importance of a healthy diet and to issue policies to improve the availability of a healthy food supply can help to reduce the rapid escalation of obesity and chronic diseases.